1984
DOI: 10.1007/bf00276976
|View full text |Cite
|
Sign up to set email alerts
|

How glucagon-like is glucagon-like peptide-1?

Abstract: Summary. Although glucagon-like peptide-1 has the appearance of a glucagon-homologue that may be co-secreted with glucagon, synthetic glucagon-like peptide-l-(1-37) does not significantly affect plasma glucose and insulin concentrations when administered at high doses (100 and 400 ~tg) to cortisone-pretreated rabbits. This synthetic preparation thus lacks the primary metabolic effect of glucagon at the doses tested. An intra-or extra-pancreatic role of glucagon-like peptide-1 has yet to be discovered. Key word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 8 publications
3
16
1
Order By: Relevance
“…In contrast to our findings, Ghiglione et al [20] failed to demonstrate a glucagon-like activity of GLP-1 in vivo in rabbits on blood glucose or plasma insulin levels, even at pharmacological doses. Two reasons could explain these negative results: First, due to the lack of interaction with the glucagon receptor in the liver [7] no effect on hepatic gluconeogenesis can be ex-pected.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, Ghiglione et al [20] failed to demonstrate a glucagon-like activity of GLP-1 in vivo in rabbits on blood glucose or plasma insulin levels, even at pharmacological doses. Two reasons could explain these negative results: First, due to the lack of interaction with the glucagon receptor in the liver [7] no effect on hepatic gluconeogenesis can be ex-pected.…”
Section: Discussioncontrasting
confidence: 99%
“…Although GLP-1(1-37) has similarities in 14 of the 37 amino acids compared with glucagon, this peptide did not elicit any insulinotropic action in anesthetized dogs, as originally reported by Ghiglione et al (1984). In contrast, a truncated peptide (7-37) revealed clearly an insulinotropic action in the present experiment, confirming the findings reported previously (Holst et al 1987 ;Mojsov et al 1987 ;Matsuyama et al 1988 ;(rskov et al 1988 ;Shima et al 1988 ;Kawai et al 1989 ;Suzuki et al 1989).…”
Section: Discussionsupporting
confidence: 90%
“…Although GLP-1 (1-37) has similarities in its amino acid sequence to glucagon, this peptide did not show any glucagon action, such as insulinotropic or glycogenolytic action (Ghiglione et al 1984). However, it has been reported that a truncated GLP-1 (7-37) elicited a strong insulin stimulating action (Mojsov et al 1987; Holst et al 1987; Shima et al 1988; Kawai et al 1989).…”
mentioning
confidence: 98%
“…GLP-l(1-36) amide did not alter blood glucose or insulin levels in fasted canines [38]. Schmidt, Siege1 & Creutzfeldt obtained a weak stimulatory effect on insulin secretion in isolated rat pancreatic islets using supraphysiological concentrations of GLP-l(1-36) amide [39], while GLP-l(1-36) amide had no insulinotropic effect in the isolated perfused pig pancreas as shown by Orskov, Holst, Knuhtsen, Baldissera, Poulsen & Vagn Nielsen [14].…”
Section: ( 3 ) Effects Of Glp-i On the Endocrine Pancreasmentioning
confidence: 82%